A native mitral valve mass beyond imagination - Alamri, Faisal; Eltayeb, Abdalla; Hamad, Alaa; Alamri, Soaad; Alamri, Sultan; Kaidali, Wassima; Tashkandi, Loay; Arbili, Lana; Pergola, Valeria; Al Sergani, Hani (Monaldi Archives for Chest Disease, 2023)
The authors report a case of a patient with a history of immunoglobulin A nephropathy who, during the admission for pneumonia, had an incidental finding of a huge mitral valve (MV) mass on transthoracic echocardiography. The differential diagnosis was challenging because the clinical scenario raised the suspicion of possible infective endocarditis, and the imaging features were suggestive of a myxoma or vegetation. The patient underwent urgent excision of the mass with MV replacement due to the high risk of embolism. Intraoperative findings were consistent with clots or vegetation. The pathology result of the thrombus was beyond our imagination, and to the best of our knowledge, only one case has been reported. Awareness about native MV thrombosis and its etiologic factors, work-up, and management is key for better medical and surgical management planning because this condition is extremely rare and challenging in the clinical and imaging arenas.